Removal of Antibiotic Drugs from Aqueous Solution by Modified Coconut Shell - Rekan M. Saeed; Rounak M. Shariff (Zanco Journal of Pure and Applied Sciences)
In this study, coconut shell (CS), coconut shell carbonized (CSC), acid coconut shell carbonized (ACSC), base coconut shell carbonized (BCSC) finally coconut shell carbonized impregnation by nickel (II) oxide (CSC/NiO) nanocomposite, investigated to remove ciprofloxacin (CIP) from an aqueous solution. Optimization of adsorption conditions: initial CIP concentration, pH, adsorbent dose and contact time were studied and found to have a significant effect on CIP removal. The morphological and chemical characteristics of the adsorbents were established by Fourier Transform Infrared (FTIR), X-Ray diffraction (XRD), The Scanning Electron Microscopy (SEM) and Energy Dispersive X-Ray (EDX). The adsorption kinetic study shows the CIP adsorption onto adsorbents follow the pseudo-second order, the values of K2, qe and R2 in the range (0.254-9.529) gµg-1min-1, (0.016-0.300) mgg-1 and (0.706-0.980) respectively at three different temperature 298 K, 308 K and 318 K. The Freundlich isotherm model adsorption data were applied and the value of KF, nF and R2 in the range (3.056-3.694) mg g-1, (1.379-1.720) and (0.886-0.999) respectively. The experimental data found to be suitable linearity with Langmuir isotherm the value of KL, Cm and R2 in the range (0.011-0.180) L mg−1, (10000-166667) μg g−1 and (0.760-0.980) respectively. The negative values of ΔGo (−18.47 to −23.74) kJ mol−l and positive value of each of ΔHo and ΔSo in the range (0.131 to 0.228) kJ mol−l and (0.992 to 1) kJ mol−lK-1 were indicating the adsorption of CIP on to adsorbents was a spontaneous and endothermic process.